Hypoxic Challenge Testing (Fitness to Fly) in children with complex congenital heart disease. Issue 16 (14th February 2018) - Naqvi, Nitha; Doughty, Victoria L; Starling, Luke; Franklin, Rodney C; Ward, Simon; Daubeney, Piers E F; Balfour-Lynn, Ian M
Abstract : Objective: Commercial airplanes fly with an equivalent cabin fraction of inspired oxygen of 0.15, leading to reduced oxygen saturation (SpO2 ) in passengers. How this affects children with complex congenital heart disease (CHD) is unknown. We conducted Hypoxic Challenge Testing (HCT) to assess need for inflight supplemental oxygen. Methods: Children aged <16 years had a standard HCT. They were grouped as (A) normal versus abnormal baseline SpO2 (≥95% vs <95%) and (B) absence versus presence of an actual/potential right-to-left (R–L) shunt. We measured SpO2, heart rate, QT interval corrected for heart rate and partial pressure of carbon dioxide measured transcutaneously (PtcCO2 ). A test failed when children with (1) normal baseline SpO2 desaturated to 85%, (2) baseline SpO2 85%–94% desaturated by 15% of baseline; and (3) baseline SpO2 75%–84% desaturated to 70%. Results: There were 68 children, mean age 3.3 years (range 10 weeks–14.5 years). Children with normal (n=36) baseline SpO2 desaturated from median 99% to 91%, P<0.0001, and 3/36 (8%) failed the test. Those with abnormal baseline SpO2 (n=32) desaturated from median 84% to 76%, P<0.0001, and 5/32 (16%) failed (no significant difference between groups). Children with no R–L shunt (n=25) desaturated from median 99% to 93%, P<0.0001, but 0/25 failed. Those with an actual/potential R–L shunt (n=43) desaturated from median 87% to 78%, P<0.0001, and 8/43 (19%) failed (difference between groups P<0.02). PtcCO2, heart rate and QT interval corrected for heart rate were unaffected by the hypoxic state. Conclusions: This is the first evidence to help guide which children with CHD need a preflight HCT. We suggest all children with an actual or potential R–L shunt should be tested.